N-Cadherin Correlates with β-Catenin Expression Across the Spectrum of Mucinous Ovarian Tumors - Mastutik, Gondo; Rahniayu, Alphania; Rahaju, Anny Setijo; Sari, Aditya Sita; Rahman, Lukman Nur; Trianto, Heru Fajar; Oey, Radianto Chandra Wijaya (Asian Pacific Journal of Cancer Biology, 2026)
Background: This study evaluates differences in N-cadherin and β-catenin expression, as well as their correlation across the histopathological spectrum of mucinous ovarian tumors, including cystadenomas, borderline tumors, and carcinomas. Methods: A cross-sectional analytical observational study was performed using 60 paraffin-embedded tissue samples from patients diagnosed with mucinous ovarian tumors (MOTs). These comprised mucinous cystadenoma (MC), mucinous borderline tumor (MB), low-grade mucinous ovarian carcinoma (MOC-LG), and high-grade mucinous ovarian carcinoma (MOC-HG). Immunohistochemical staining was then performed to evaluate N-cadherin and β-catenin expression, which was analyzed according to the H-score system. Results: The results demonstrated that N-cadherin expression differed significantly across the MOTs spectrum, with significant pairwise differences between MC and MOC-LG, MC and MOC-HG, and MB and MOC-HG. β-catenin expression also varied significantly across tumor types, with significant differences between MC and MOC-LG (p = 0.001), MC and MOC-HG, MB and MOC-LG, and MB and MOC-HG. In addition, a positive correlation was observed between N-cadherin expression and the MOTs spectrum (r = 0.422) as well as between β-catenin expression and the MOTs spectrum (r = 0.603). N-cadherin expression showed a significant positive correlation with β-catenin expression across the MOTs spectrum (r = 0.487). Conclusion: N-cadherin was significantly correlated with β-catenin across the MOTs spectrum. These results suggested that N-cadherin and β-catenin may serve as potential histopathological diagnostic markers for distinguishing among the benign, borderline, and malignant spectra of MOTs and provide a molecular basis for further investigation into their roles in cancer invasion and metastasis.